2008
DOI: 10.1007/s10228-008-0062-1
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic shift in dietary preference and low dietary overlap in rohu (Labeo rohita) and common carp (Cyprinus carpio) in semi-intensive polyculture ponds

Abstract: In order to investigate ontogenetic changes in diet and diet overlap between rohu (Labeo rohita) and common carp (Cyprinus carpio) in polyculture ponds, food preferences of different size classes of these fishes were quantified. Rohu diet consisted of both phytoplankton and zooplankton, and there was a distinct ontogenetic shift in the relative importance of these food items. Zooplankton was the dominant food for rohu up to 20.6 cm total length (TL) and then gradually decreased in importance as fish grew. Phyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 23 publications
1
26
0
2
Order By: Relevance
“…carp than by later developmental stages (cf. Rahman et al 2009). Benthic macroinvertebrates constituted an important component of the diet as early as at an individual fish size of 3-5 cm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…carp than by later developmental stages (cf. Rahman et al 2009). Benthic macroinvertebrates constituted an important component of the diet as early as at an individual fish size of 3-5 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Although carp diets, both in natural and aquaculture conditions, and the influence of carp on water quality have been widely studied (e.g. Matlak and Matlak 1976;Crivelli 1981;Vilizzi 1998;Rahman et al 2009), the consequences of carp impacts on the biotic and abiotic characteristics of aquacultural systems have received attention only with regard to the intensification of fish production (Pechar 2000;Potužák et al 2007) and pond suitability for viable polycultures with other fish species (reviewed in Kestemont 1995;Rahman et al 2009). Elucidation of the potential differences in age-structured carp effects on pond ecosystem properties, such as water turbidity, is crucial for understanding how to manage available pond resources so as to support functions other than fish production, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This is in accordance with the study of Ć irić et al (2015), who observed significantly higher mean hardness (and consequently conductivity) in ponds provided with PF rather than CG, which they also attributed to a higher content of calcium. Regarding natural food, although adult carp mainly ingest benthic macroinvertebrates, zooplankton, especially large-bodied organisms such as Daphnia, can also form a large part of the diet as the branchial sieve retains organisms > 0.25 mm (Sibbing et al 1986, Rahman et al 2009, Anton-Pardo et al 2014. Carp occasionally reduce the abundance of largebodied zooplankton indirectly through increased turbidity, as high turbidity inhibits phytoplankton development and its ingestion by planktonic filter feeders.…”
Section: Discussionmentioning
confidence: 99%
“…Common carp only feed on algae to a minor degree and prefers artificial feed, macroinvertebrates and zooplankton, if available (Rahman et al, 2009). In contrast, tilapia which constituted the main part of the fish population in the present study, have been reported to be able to control algae biomass in ponds by efficient grazing (Rahman et al, 2008).…”
Section: Inmentioning
confidence: 99%